Does Family Migration Affect Access to Public Health Insurance? Medical Insurance Participation in the Context of Chinese Family Migration Flows - Liu, Luchan (Frontiers in Public Health, 2021)
Using 2017 Migrant Dynamic Survey (CMDS) data, logistic regression models were developed to explore the family migration rate on health care participation of floating population. The analysis reveals that 68.69% of the floating population in China moves with at least one family member, but the local health insurance participation rate of them are relative low. However, family migration rate has a significant positive correlation with the health insurance participation of the floating population at the destination, which explains by family support and social integration mechanisms. The higher the degree of family migration, the higher the likelihood of participating in local health insurance system. Age, labor contract types, migration range and cities numbers, health records and the accessibility of health resources have a significant negative correlation with health care participation of the floating population at the destination; gender, health, marriage, education, hukou types, monthly income, migration history and move duration have a significant positive correlation. The effect of family migration rate on health care participation is weaker in group in which people are low-educated and signs nonfixed-term contract or gets bottom 50% monthly income or under the no-kids family structure. Potential policies informed by these findings are also explored.